Singing the Classical, Voicing the Modern : The Postcolonial Politics of Music in South India - Weidman, Amanda J., 1970- (Book collections on Project MUSE., 2006)
An ethnographic history and critique of the emergence of South Indian carnatic music as a "classical" music in the 20th century.